The model construction in airport renewable energy system scale planning based in Multi-Criteria Decision Making - Qin Jia (Elsevier, 2021)
In order to solve the energy consumption and environmental problems, renewable energy was utilized in many airports. However, due to the periodic and intermittent, a single renewable energy generation is difficult to provide a continuous supply all the time. Hybrid energy system was considered to be the important way to alleviate the intermittent. The study focuses on the optimal design of hybrid renewable energy system planning. A model based on Multi-Criteria Decision Making (MCDM) was constructed. This model could achieve the optimization of scale for renewable energy and energy storage devices in hybrid renewable energy. The model was built in consideration of different power grid operation strategies including “Independence-net operation” and “grid connected operation”. The results showed that the environmental and social benefits could be calculated at the same time, and the optimal renewable energy system scale planning outcome could be obtained.